EDUARD HANSLICK: “THE BEAUTIFUL IN MUSIC” – AN AESTHETICS OF THE ABSOLUTE MUSIC - Attila FODOR (Studia Universitatis Babeş-Bolyai. Musica)
Around the middle of the 19th century, musical critic and professor of Vienna University, Eduard Hanslick, was going to publish a polemical treatise about musical aesthetics entitled The beautiful in music, proclaiming the necessity of a substantial reappraisal of this discipline. Despite the remarkable notoriety gained by Hanslick’s treatise, his initiative seems to be neither new, nor original, as the approach of his treatises’ central idea – the concept of absolute music – had already entered numerous debates and discussions launched a century before, giving rather a particular view than a systematic clarification of it. In the center of the hanslickian debates are situated, on the one hand, the negation of traditional aesthetic views, which designated as the object of music the emotions, affects, morale, character and programme music, and on the other the construction of an aesthetic system based on the immanence of musical structure through a quasi-exclusive concentration on the concept of form, both in creation and reception. In spite of its scientific pragmatism, Hanslick’s treatise denotes the continuous presence of an undeclared philosophical substratum, becoming basically the aesthetic foundation of instrumental music, considered by its author the superior expression of this art.